Experimental Investigation of a Regenerative Kalina Cycle for Electrical Power Generation Using Waste Heat - Nassir, Abdulkhodor K.; Shahad, Haroun A. K. (Journal of Petroleum Research and Studies, 2024)
Kalina cycle is a thermodynamic power cycle uses any waste heat source (low temperature source) to generate electrical power or cooling. Many versions of Kalina cycle exist. In this paper a regenerative Kalina version is designed and constructed. The cycle consists of the following main components: heat recovery vapor generator (HRVG), separator, turbine, condenser, throttling valve, mixer (absorber), heat exchanger and pump. The heat exchanger is used to heat the working fluid coming from the pump before entering the HRVG by the hot saturated liquid (weak solution) coming from the separator. The cycle uses aqua ammonia mixture as the working fluid with different ammonia concentrations. The effect of many operating conditions on cycle performance is studied such as ammonia (NH3) mass fraction (range from 0.85-0.89), low pressure (range from 2-4 bar), and maximum pressure (range from 20-40 bar). The dryness fraction (DF) at separator entrance is kept at 0.3. The results show that the highest thermal efficiency obtained is 12.9% at Pmax=35 bar, Pmin=2 bar, and x=0.85. The highest value of the net power is 0.367 kW at x=0.89 at turbine inlet pressure of Pmax=20 bar. The highest value of exergy efficiency is 28.5% at Pmax=35 bar, Pmin=2 bar. It is noticed that the highest exergy destruction is in the heat recovery vapor generator (HRVG) which is about 48% due to high temperature heat exchange process and low mass flow rate. The exergy destruction is larger at Pmax=35 and x=0.89 than the exergy destruction at Pmax=20 bar and x=0.89.